Inventory of European Sea Bass (Dicentrarchus labrax) sncRNAs Vital During Early Teleost Development - Sarropoulou, Elena; Kaitetzidou, Elizabet; Papandroulakis, Nikos; Tsalafouta, Aleka; Pavlidis, Michalis (Frontiers in Genetics, 2019)
During early animal ontogenesis, a plethora of small non-coding RNAs (sncRNAs) are greatly expressed and have been shown to be involved in several regulatory pathways vital to proper development. The rapid advancements in sequencing and computing methodologies in the last decade have paved the way for the production of sequencing data in a broad range of organisms, including teleost species. Consequently, this has led to the discovery of sncRNAs as well as the potentially novel roles of sncRNA in gene regulation. Among the several classes of sncRNAs, microRNAs (miRNAs) have in particular been shown to play a key role in development. The present work aims to identify the miRNAs that play important roles during early European sea bass (Dicentrarchus labrax) development. The European sea bass is a species of high commercial impact in European and especially in Mediterranean aquaculture. This study reports, for the first time, the identification and characterization of the small RNAs that play a part in the ten developmental stages (from morula to all fins) of the European sea bass. From ten developmental stages more than 135 million reads, generated by next-generation sequencing (NGS), were retrieved from publicly available databases as well as newly generated. The analysis resulted in about 2,000 sample grouped reads, and their subsequently annotation revealed that the majority of transcripts belonged to the class of miRNAs followed by small nuclear RNAs and small nucleolar RNAs. The analysis of small RNA expression among the developmental stages under study revealed that miRNAs are active throughout development with the main activity occurring after the earlier stages (morula and 50% epiboly) and at the later stages (first feeding, flexion and all fins). Furthermore, investigating miRNAs exclusively expressed in one of the stages unraveled five miRNAs with a higher abundance only in the morula stage (miR-155, miR-430a, d1, d2 and miR458), indicating possible important key roles of those miRNAs in further embryonic development. An additional target search showed putative miRNA-mRNA interactions with possible direct and indirect regulatory function of the identified miRNAs.